HUMANIZATION IN THE SHORT STORY ‘DATANGNYA DAN PERGINYA’ A. A. NAVIS: A CRITICAL DISCOURSE ANALYSIS - Jusrin Efendi Pohan (Linguistik : Jurnal Bahasa dan Sastra, 2026)
The focus of this research is a discourse analysis of women's positions in the short story Datangnya dan Perginya by AA Navis. This discourse analysis aims to examine the author's ideology with the subject-object positions in the short story. This research was conducted qualitatively with an emphasis on the description of critical discourse analysis of the short story Datangnya dan Perginya by AA Navis. Critical discourse analysis framework aims to examine the position of women in a text, as they are often placed in a disadvantaged position. The portrayal of the actors' positions refers to the actions of the story's subjects and objects. The short story's author wants readers to side with humanity. This siding with humanity, on the other hand, will override any sense of divinity. This bias can be seen from the analysis of the subject-object position, which mostly places the character of Masri's father in the subject position, who from the beginning of the story is struggling with humanitarian issues such as love, affection, and sexuality.